(untitled) (Global Journal of Medical Research, 2015)
The study assessed the influence of clinic-based health education on women’s knowledge and attitudes in relation to pregnancy management in Ogun State. Stratified sampling method was used to allocate 48 pregnant women each to experimental and control groups, making a total of 96 respondents. Structured questionnaire was used to gather data from the respondents. The women in the experimental group were exposed to two hours of health education discussion addressing pertinent maternal health issues weekly for five weeks. Data were analyzed using descriptive statistics and independent t-test. All tests were measured at p≤0.05 level of significance.